2020
DOI: 10.1002/brb3.1931
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non‐CNS childhood cancer on resting‐state connectivity and its association with cognition

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Our findings suggest that CNS involvement is a key risk factor that predicts cognitive outcomes. However, our own research shows that cerebral alterations on the level of resting-state functional networks are altered even in CC survivors without CNS involvement (Spitzhüttl et al, 2020). Past studies have found that age at diagnosis is linked to cognitive functioning (Mulhern & Palmer, 2003;Mulhern et al, 2004;Sands et al, 2001).…”
Section: Clinical Risk Factorsmentioning
confidence: 66%
“…Our findings suggest that CNS involvement is a key risk factor that predicts cognitive outcomes. However, our own research shows that cerebral alterations on the level of resting-state functional networks are altered even in CC survivors without CNS involvement (Spitzhüttl et al, 2020). Past studies have found that age at diagnosis is linked to cognitive functioning (Mulhern & Palmer, 2003;Mulhern et al, 2004;Sands et al, 2001).…”
Section: Clinical Risk Factorsmentioning
confidence: 66%
“…ACE‐III includes tests of attention, orientation, memory, fluency, language and visuospatial abilities, with a maximum score of 100. Although ACE‐III is employed commonly as a Dementia screening tool, it was selected because fronto‐temporal areas play a role in mediating execute functions 11 and compromise in executive functions have been reported in sarcoma patients undergoing chemotherapy 12 . Nevertheless this assessment has not been utilized in younger patients, it should be noted that we have used raw scores rather than normative scores for comparison of neuropsychological assessment among groups.…”
Section: Methodsmentioning
confidence: 99%